An Error Analysis of Students’ Paragraphs and Essays: A Case of First-Year Students of an English Medium University in Bangladesh - Rahman, Md Momtazur (International Journal of Language and Literary Studies, 2022)
Writing is deemed an enticing task in second language learning. Most researchers reason that second-language speakers of English not only find difficulty in writing tasks but speakers whose first language is English also face problems in writing. Therefore, the ability to communicate viably in English by both second language speakers and native speakers requires comprehensive and specific instruction. It is obvious that writing plays an integral role in student’s academic life, and academic writing in English has brought considerable attention in English medium universities in Bangladesh. So, the International University of Business Agriculture and Technology (IUBAT) is no exception. This university, a non-government tertiary level and English medium institution in the country emphasize English’s importance in producing its graduates from its inception. Writing is a productive skill; as an instructor at this university, I identify students’ difficulty writing compositions. In this paper, I explored the writing errors in a corpus of 30 paragraphs and 15 essays written by first-year students of IUBAT. The findings revealed that students have to face the serious challenges of writing error-free compositions even after completing the two English proficiency courses. Out of the 45 scripts that were analyzed, 96 errors were identified. The study further revealed that 66 of these total errors were related to grammatical errors and poor structuring of sentences. 28 errors were related to the mechanics of writing. The findings of the study direct recommendations and implications for educators, policymakers, and curriculum developers. This study has repercussions for pedagogy and future research in error analysis.